An Analytical Study on Pre & Post Covid -19 Changes of Inflation and Interest Rate affects on Home Loan - Baswani, Srishti; Banerjee, Sudip (Journal of Advanced Research in Humanities and Social Sciences, 2024)
The coronavirus pandemic, which has changed the lives of millions of people worldwide, has been a triggering aspect for every individual in the world. The world economy is affected by the pandemic, which resulted in a recession in the market as the income of the individual got affected, and with low income in hand, there is less home loan buying in the industry. Through government-provided data on the inflation rate and amount of home loans disbursed with SBI home loan interest rates, the study analyses how changes in inflation and interest rates pre- and post-COVID-19 pandemic affected home loans from FY 2017-18 to FY 2022-23.